Turtle anoxia tolerance: Biochemistry and gene regulation - Krivoruchko, Anastasia; Storey, Kenneth B. (Biochimica et biophysica acta, 2015)
While oxygen limitation can be extremely damaging for many animals, some vertebrates have perfected anaerobic survival. Freshwater turtles belonging to the Trachemys and Chrysemys genera, for example, can survive many weeks without oxygen, and as such are commonly used as model animals for vertebrate anoxia tolerance. In the present review we discuss the recent advances made in understanding the biochemical and molecular nature of natural anoxia tolerance of freshwater turtles. Research in recent years has shown that activation of several important pathways occurs in response to anoxia in turtles, including those that function in the stress response, cell cycle arrest, inhibition of gene expression and metabolism. These likely contribute to anoxia tolerance in turtle tissues by minimizing cell damage in response to anoxia, as well as facilitating metabolic rate depression. The research discussed in the present review contributes to the understanding of how freshwater turtles can survive without oxygen for prolonged periods of time. This could also improve understanding of the molecular nature of hypoxic/ischemic injuries in mammalian tissues and suggest potential ways to avoid these. •Biochemical and molecular mechanisms of natural anoxia tolerance of turtles are reviewed.•Several stress-responsive pathways have been shown to be activated in response to anoxia.•Pathways involved in cell cycle arrest are also anoxia-responsive.•Strong constitutive and inducible antioxidant defenses are important for anoxic survival.•Several mechanisms involved in suppression of global gene expression are activated.